2017
DOI: 10.1016/j.aquatox.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contaminants of emerging concern on liver mitochondrial function in Chinook salmon

Abstract: We previously reported the bioaccumulation of contaminants of emerging concern (CECs), including pharmaceuticals and personal care products (PPCPs) and perfluorinated compounds, in field-collected juvenile Chinook salmon from urban estuaries of Puget Sound, WA (Meador et al., 2016). Although the toxicological impacts of CECs on salmon are poorly understood, several of the detected contaminants disrupt mitochondrial function in other species. Here, we sought to determine whether environmental exposures to CECs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…This could provide an explanation for the detected decreases in the Krebs cycle metabolites in oysters exposed to diphenhydramine at this time point; however, ATP levels were not quantified in the present study. Supporting this hypothesis, chinook salmon ( Oncorhynchus tshawytscha ) exposed to a chemical mixture (that included both diphenhydramine and fluoxetine) showed increases in liver mitochondria respiration rates and a reduction in total mitochondrial glutathione, suggesting reductions in ATP synthesis, metabolic capacity, and oxidative stress (Yeh et al ).…”
Section: Resultsmentioning
confidence: 96%
“…This could provide an explanation for the detected decreases in the Krebs cycle metabolites in oysters exposed to diphenhydramine at this time point; however, ATP levels were not quantified in the present study. Supporting this hypothesis, chinook salmon ( Oncorhynchus tshawytscha ) exposed to a chemical mixture (that included both diphenhydramine and fluoxetine) showed increases in liver mitochondria respiration rates and a reduction in total mitochondrial glutathione, suggesting reductions in ATP synthesis, metabolic capacity, and oxidative stress (Yeh et al ).…”
Section: Resultsmentioning
confidence: 96%
“…First, we can minimize or continue to ban contaminants, such as polychlorinated biphenyls (PCBs), that persist in riverine and estuarine food webs years after chemical use is discontinued (e.g., West, O'Neill, & Ylitalo, 2017). In particular, Chinook salmon near wastewater treatment plants accumulate many contaminants of emerging concern (Meador et al, 2016), including some that impair liver mitochondrial function (Yeh, Marcinek, Meador, & Gallagher, 2017 (Lamb et al, 2017;Lotze et al, 2006). Managing water flow is an ongoing challenge in coastal systems worldwide, and maintaining a balance between human needs (e.g., water consumption and diversion; Cloern & Jassby, 2012), and fish health will be key to sustaining coastal ecosystem services.…”
Section: Discussionmentioning
confidence: 99%
“…PCBs), that persist in riverine and estuarine food webs years after chemical use is discontinued (e.g.,West, O'Neill, & Ylitalo, 2017). In particular, Chinook salmon near wastewater treatment plants accumulate many contaminants of emerging concern(Meador et al, 2016), including some that impair liver mitochondrial function(Yeh, Marcinek, Meador, & Gallagher, 2017). Next, we can conserve or restore biogenic fish habitats (e.g., seagrass meadows, oyster reefs) that maintain water quality for coastal F I G U R E 5 Predicted CPUE, when present, of English sole among estuaries.…”
mentioning
confidence: 99%
“…Personal care products. PPCPs have been widely detected in different ecosystems worldwide and are recognized as contaminants of concern, their environmental toxicology has also been highlighted Based on the microscopic analysis, it was reported that exposure to contaminants of emerging concern can affect both mitochondrial quality and content, particularly in liver, resulting in sublethal effects on wild fish (Yeh et al 2017). The study of Hoobin et al Another study revealed that the mobile genetic elements were abundant in sludge from wastewater treatment plants, which was likely important for the acquisition and mobility of various ARGs among the bacterial species and increased the risk of ARG horizontal transfer (Guo et al 2017).…”
Section: Environmental Toxicitymentioning
confidence: 99%